2013
DOI: 10.1177/1032373213505167
|View full text |Cite
|
Sign up to set email alerts
|

Improving accounting and accountability in local governments: The case of the Tennessee Taxpayers Association

Abstract: While comprehensive auditing of federal government agencies in the United States had its inception in 1945, citizen-led efforts to evaluate and improve state and local government operations began much earlier. One such early pioneer organization was the Tennessee Taxpayers Association (TTA). Using group theory constructs from the political science field, this study documents how the TTA was able to use its power and influence to shape the development of accounting systems and accountability in the local govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…Those findings are also in line with the work of some researches (Gooden & Rissler, 2017;Jurnali & Siti-Nabiha, 2015;Porumbescu, 2015;Pridgen & Flesher, 2013;Rosa & Morote, 2016) which showed that the gradual application of the principle of accountability will finally support public trust regarding the administration of village development. It will eventually reach the level of village community participation which cumulatively will support the success of the regional development.…”
Section: Resultssupporting
confidence: 86%
“…Those findings are also in line with the work of some researches (Gooden & Rissler, 2017;Jurnali & Siti-Nabiha, 2015;Porumbescu, 2015;Pridgen & Flesher, 2013;Rosa & Morote, 2016) which showed that the gradual application of the principle of accountability will finally support public trust regarding the administration of village development. It will eventually reach the level of village community participation which cumulatively will support the success of the regional development.…”
Section: Resultssupporting
confidence: 86%
“…Village development requires village trust, considering that community trust strongly encourages the community to actively participate in accelerating village development (Dewi & Adi, 2019;Sofyani et al, 2018). Previous research revealed that increase community participation in the development planning process needs to be based on shared interest and community awareness of the importance of participation in village development (Junne, 2018;Pridgen & Flesher, 2013). However, people's trust in the government as the implementer of a policy tends to decrease, some even say that the government is no longer needed.…”
Section: Figure 1 Good Governance Principles In Village Fund Managementmentioning
confidence: 99%
“…4 The connection between LG and other local bodies, particularly EIs, is the subject of this study in light of the important role of accounting and accountability ‘in the administration and governance of such organizations and, consequently, in the process of ordering activities within local communities’ (Gomes and Sargiacomo, 2013: 439). In particular, this study focusses on the accounting interrelationship between LGs and non-business and non-governmental associations, which resulted from citizens’ efforts to improve state and LG operations (Daniels et al, 2010; Pridgen and Flesher, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%